What is professional learning about? Framing an educational point of view - Alves, Mariana Gaio (Revista Interacções, 2014)
The paper’s main goal is to sketch an approach to professional learning that allows for a deeper understanding of its dynamics, dimensions and challenges. In doing so, an educational point of view is adopted whereby: (a) the focus is on the process of learning to be a professional; (b) this process is understood as the result of an interaction between individuals, knowledge and different learning contexts (schools, universities, work organisations); and (c) this process is not a mere rational exercise because it involves diverse dimensions such as emotions and beliefs as well as cultural and social engagements.